The Teachings of Confucius: A Humanistic Adult Education Perspective - Kuing Ryu (Adult Education Research Conference, 2008)
Confucianism is an ancient philosophical system that has much to offer in terms of teachings about education and adulthood. This paper explores ethical values and key principles that help define the philosophical basis of Confucianism, and provides comparative approaches between Confucianism as a humanistic philosophical system and the Western context of humanistic adult education.
Keywords: confucianism; humanistic adult education; humanism; educational philosophy